ANALISA VARIASI PEMBELAJARAN PADA MAHASISWA PROGRAM MAGISTER PENDIDIKAN IPA UNIVERSITAS MATARAM - KOSIM -; Susilawati -; Aris Doyan; Ahmad Harjono (Jurnal Penelitian Pendidikan IPA, 2017)
Descriptive study was conducted in order to determine the level of variation of instruction for student of Master of Science Education Program at University of Mataram. Important research carried out in connection with one of the competencies of teaching skills as a graduate Master of Science Education. Data collection method for the analysis of variations in instruction styles questionnaire used learning and teaching as well as a process for learning with multi representation approach on the subject of wave phenomena The population as well as a sample are students of Master of Science Education 2015/2016 and 2016/2017. The results of data processing of the variety of instruction based teaching style show 34.35% visual, 31.71% auditory and 33.94% kinestetic. While the level of variation of Instruction based on a total score of 45.50% in good category. Results variety of instruction with a multi representation provides a good level of 50.00%.Keywords: Variation of Instruction, Teaching style, Multi Representation Approach